Defending Community, Territory, and Indigenous Environmental Relations - Gahman, Levi; Penados, Filiberto; Coc, Cristina; Smith, Shelda-Jane (Cambridge University Press, 2026)
This Element addresses a range of pressing challenges and crises by introducing readers to the Maya struggle for land and self-determination in Belize, a former British colony situated in the Caribbean and Central America. This title is also available as open access on Cambridge Core.